Sustainable Agriculture for Climate Change Adaptation - Lewis, Kathy; Warner, Douglas (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Anthropocene, the time of humans. Never has human influence on the functioning of the planet been greater or in more urgent need of mitigation. Climate change, the accelerated warming of the planet's surface attributed to human activities, is now at the forefront of global politics. The agriculture sector not only contributes to climate change but also feels the severity of its effects, with the water, carbon and nitrogen cycles all subject to modification as a result. Crop production systems are each subject to different types of threat and levels of threat intensity. There is however significant potential to both adapt to and mitigate climate change within the agricultural sector and reduce these threats. Each solution must be implemented in a sustainable manner and tailored to individual regions and farming systems. This Special Issue evaluates a variety of potential climate change adaptation and mitigation techniques that account for this spatial variation, including modification to cropping systems, Climate-Smart Agriculture and the development and growth of novel crops and crop varieties.